2013
DOI: 10.3109/00207454.2013.783030
|View full text |Cite
|
Sign up to set email alerts
|

Racial-ethnic differences in stroke risk factors and subtypes: results of a prospective hospital-based registry

Abstract: A majority of stroke research in the United States focuses on Caucasian and African-American populations, limiting the amount of comparative stroke data available on other racial and ethnic groups. The purpose of this research was to examine differences in stroke risk factors/subtypes between minority stroke patient groups in the United States (Asian-Indian, African-American, and Hispanic), using a Caucasian reference group. All patients had a comprehensive stroke work-up to ascertain their stroke risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…27 South Asian individuals tend to present with acute first stroke at a younger age than East Asian and white individuals. 32,33 The increased risk of stroke in South Asians is associated with greater mortality. 29 A systemic review showed that the standardized mortality ratio for ischaemic stroke in South Asians was 55% and 41% greater in men and women, respectively, compared with the white population, a difference Key points ■ Although few prospective studies of atrial fibrillation (AF) epidemiology in Asian countries have been conducted, AF prevalence is thought to be lower in Asians than in white populations ■ However, Asian individuals seem to be at a higher risk of stroke, and have greater stroke-related morbidity and mortality, than white individuals ■ Asian individuals seem to be at particularly high risk of haemorrhagic stroke and intracranial haemorrhage, which has discouraged the widespread uptake of warfarin in Asian patients with AF ■ Antiplatelet agents have been overused for primary stroke prevention in Asian patients with AF, in whom these drugs are neither safe nor effective ■ Non-vitamin K antagonist anticoagulants are noninferior to warfarin for stroke prevention in AF, and are associated with a reduced incidence of haemorrhagic stroke and intracranial haemorrhage compared with warfarin ■ The efficacy and safety profile of non-vitamin K antagonist anticoagulants in randomized, controlled trials suggest these drugs have great potential as anticoagulants in Asian individuals with AF consistent across Indian, Pakistani, and Bangladeshi ethnic ities.…”
Section: Af and Stroke Epidemiology In Asiansmentioning
confidence: 99%
“…27 South Asian individuals tend to present with acute first stroke at a younger age than East Asian and white individuals. 32,33 The increased risk of stroke in South Asians is associated with greater mortality. 29 A systemic review showed that the standardized mortality ratio for ischaemic stroke in South Asians was 55% and 41% greater in men and women, respectively, compared with the white population, a difference Key points ■ Although few prospective studies of atrial fibrillation (AF) epidemiology in Asian countries have been conducted, AF prevalence is thought to be lower in Asians than in white populations ■ However, Asian individuals seem to be at a higher risk of stroke, and have greater stroke-related morbidity and mortality, than white individuals ■ Asian individuals seem to be at particularly high risk of haemorrhagic stroke and intracranial haemorrhage, which has discouraged the widespread uptake of warfarin in Asian patients with AF ■ Antiplatelet agents have been overused for primary stroke prevention in Asian patients with AF, in whom these drugs are neither safe nor effective ■ Non-vitamin K antagonist anticoagulants are noninferior to warfarin for stroke prevention in AF, and are associated with a reduced incidence of haemorrhagic stroke and intracranial haemorrhage compared with warfarin ■ The efficacy and safety profile of non-vitamin K antagonist anticoagulants in randomized, controlled trials suggest these drugs have great potential as anticoagulants in Asian individuals with AF consistent across Indian, Pakistani, and Bangladeshi ethnic ities.…”
Section: Af and Stroke Epidemiology In Asiansmentioning
confidence: 99%
“…8-10 Specifically, higher proportion of small vessel disease (SVD)/lacunar stroke and intracranial atherosclerosis have been described among minorities. 9-12 Establishing these disparities in ischemic stroke subtypes is important in understanding the predominant stroke mechanism among the high-risk ethnic group, which may result in more focused primary and secondary stroke prevention strategy for that community.…”
Section: Introductionmentioning
confidence: 99%
“… 7 11 However, no DWI‐based study has investigated the global relationships between vascular territories in which stroke lesions occur and stroke mechanisms, and these relationships have not been reported for Asian populations, for which stroke mechanisms may be different from those in Western countries. 12 In this study, the Trial of ORG 10172 in Acute Stroke Treatment, or TOAST, classification 1 of stroke subtypes was adopted and related to the vascular territories of acute ischemic lesions detected by DWI in ischemic stroke patients. In addition, we intended to provide practical information about the distribution of stroke mechanisms according to invaded vascular territories.…”
Section: Introductionmentioning
confidence: 99%